PETROGLYPHS AND PILLARS: A COMPREHENSIVE STUDY OF ROCK ENGRAVINGS AND SCULPTURES IN NORTH GUWAHATI, ASSAM - Pathak, Guptajit (International Journal of Research -GRANTHAALAYAH, 2020)
Situated on the northern banks of the Brahmaputra River, North Guwahati is an important but little-studied archeological area in Assam. Numerous stone sculptures and carvings (petroglyphs) that represent various religious, cultural, and artistic traditions spanning several centuries may be found in the vicinity. These sculptures and petroglyphs are significant not only for their aesthetic and symbolic value but also for their capacity to shed light on early Assam socio-cultural and historical dynamics (Hazarika, 2018, pp. 45-49). These sculptures and engravings of rocks have not gotten any systematic scholarly attention, despite their importance. Smaller and scattered petroglyphs have not received enough attention because earlier research has mostly concentrated on important temples and historical locations.² In order to provide a thorough cultural and historical map of North Guwahati's lesser-known legacy, the current study conducts an extensive assessment of these rock inscriptions, carvings, and pillars to examine their creative styles, motifs, religious affiliations, and spatial distribution. In order to understand the historical context of these monuments, this study also highlights the significance of combining archaeological evidence with oral traditions and local tales. The research aims to contribute to cultural tourism, heritage preservation, and a wider understanding of Assam's ancient and medieval history by recording and examining the petroglyphs and sculptures. It also highlights the importance of these tangible and intangible cultural resources for both academics and local communities.